Implementasi Peraturan Bupati Nomor 47 Tahun 2018 Tentang Pembatasan Waktu Oprasional Mobil Angkutan Tanah Pada Ruas Jalan Kecamatan Kresek Kabupaten Tangerang - Hidayat, Ahmad Dodi; Bahrudin, Febrian Alwan; Nida, Qotrun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study examines the problem of the implementation planning process, implementation and results of the implementation of Regent Regulation No. 47 of 2018 concerning restrictions on the operational time of land transport cars on the roads of Kresek district, Tangerang regency. The purpose of this study was to determine the process of planning, implementation and results of Regent Regulation No. 47 of 2018 concerning restrictions on the operational time of Land Transportation cars on the roads of Kresek district, Tangerang regency. The research method used is descriptive method using qualitative approach by conducting interviews. The results of this study indicate that the planning process for the implementation of Regent Regulation No. 47 of 2018 concerning restrictions on the operational time of land transport cars on the roads of Kresek subdistrict, Tangerang regency, is based on the Regent's policy so that the state conditions in the tangerang Regency area can reduce the problems that occur, the implementation of most, less dust and slippery roads when it rains and less traffic accidents.